Inflammation is associated with pain and fatigue in older adults - Sara A. Norton; Lauren M. Blaydon; Megan Niehaus; Alex P. Miller; Patrick L. Hill; Thomas F. Oltmanns; Ryan Bogdan (Brain, Behavior, & Immunity - Health)
Introduction: Increasing evidence suggests that inflammation may play a pivotal role in the development of chronic pain and fatigue in aging individuals. This study investigated the relationship between three inflammatory markers (IL-6, CRP, and TNFα) and pain and fatigue, both cross-sectionally and longitudinally, in a sample of older adults from the Saint Louis Personality and Aging (SPAN) study. Methods: SPAN study participants provided blood samples at two in-person sessions approximately 2 years apart for the analysis of the inflammatory biomarkers IL-6, CRP, and TNFα. Pain and fatigue were assessed using the RAND-36 Health Status Inventory. Correlations (with false discovery rate correction for multiple testing) and follow-up linear regressions including potentially confounding demographic (e.g., annual household income) and health (e.g., BMI, medication use) covariates were used to estimate cross sectional and longitudinal associations. Analytic ns ranged from 533 to 815. Results: Cross-sectional analyses revealed that higher IL-6 and CRP were associated with greater reported pain and fatigue, even after accounting for covariates (βs > .098, ps < .05). TNFα was associated with greater fatigue only (β = .100, p = .012). Longitudinally, CRP and IL-6 predicted future pain and fatigue, although only the relationship between CRP and future fatigue survived the inclusion of covariates (β = .104, p = .022). Both pain and fatigue predicted higher levels of IL-6 and CRP approximately 2 years later, although only the associations with IL-6 survived the inclusion of covariates (βs > .12, ps < .01). Discussion: Our study adds to a growing body of literature showing that inflammation is associated with greater pain and fatigue in older adults. Our longitudinal data showing temporal bidirectional associations is consistent with evidence from non-human animal models that heightened inflammation causally contributes to fatigue and also suggests that the experience of pain and fatigue may contribute to inflammation. It will be important for future work to identify how lifestyle factors associated with pain and fatigue (e.g., physical activity) may contribute to these associations.